Project track and trace ontology - Dong, Hai; Hussain, Farookh; Chang, Elizabeth (IEEE, 2007)
It is well-known that ontology is utilized as an effective methodology to share domain-specific knowledge in multidisciplinary fields. In the field of project management, due to the characteristic of project organizations in which project members are geographically dispersed and from different cultural background, senior management would feel difficulty when they attempt to know about the detailed project completion status from dispersed project groups. Thus, the objective of this paper is to propose an automated project track and trace methodology through the use of ontology technology, to challenge the knowledge sharing issues in project organizations. By means of extending CCCI Metrics into the field of project management and introducing a new ontological notation system, we deliver the project track and trace ontology.